Initial stages of hand osteoarthritis do not affect the extrinsic muscles of the hand: a cross-sectional study - Natália Barbosa Tossini; André Luis Simões Zacharias; Luiza Souza Seraphim Abrantes; Paula Regina Mendes da Silva Serrão (Scientific Reports, 2021)
Abstract The objective of this study was to verify whether women in the initial stages of hand osteoarthritis (HOA) already have impaired grip strength and flexor and extensor torque of the wrist compared to healthy women. It also aimed to correlate these variables with pain, stiffness, and function of the hand. Twenty-six women were divided into a control group [CG, n = 13; 56 (51–61) years old] and a hand osteoarthritis group [HOAG, n = 13; 58 (53–63) years old]. Grades II and III were included in the HOA group according to the criteria of Kellgren and Lawrence. All volunteers answered an initial assessment form, the Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire and the Australian/Canadian Hand Osteoarthritis Index (AUSCAN). The grip strength and isometric wrist flexor and extensor torque were evaluated by a hydraulic dynamometer. Comparisons between groups used Student’s t test for independent samples and the Mann–Whitney test. Spearman's correlation was used to correlate grip strength and flexor and extensor wrist torque to the degree of disease and DASH and AUSCAN scores. There were no differences between the groups in grip strength or flexor and extensor torque values. In terms of the DASH and the AUSCAN, the HOA group had higher scores, indicating worse hand function. A strong negative correlation was found between grip strength and the degree of HOA (r =  − 0.70, p = 0.008), and a moderate positive correlation was found between flexor torque and the degree of HOA (r = 0.53, p = 0.05). The pain (r =  − 0.61, p = 0.02) and function (r =  − 0.66, p = 0.01) sections of the AUSCAN correlated negatively with grip strength. Pain can be an important feature in the HOA rehabilitation process, as it can influence handgrip strength and function. It is important that rehabilitation is implemented as soon as possible to guarantee the maintenance of strength and function since with the severity of the disease, patients tend to have deficits in grip strength and function.